Advanced Inversion Techniquesfor Ground Penetrating Radar - Alessandro Fedel; Matteo Pastorino; Andrea Randazzo (Journal of Telecommunications and Information Technology, 2017)
Ground Penetrating Radar (GPR) systems arenowadays standard inspection tools in several application areas, such as subsurface prospecting, civil engineering and cultural heritage monitoring. Usually, the raw output of GPR isprovided as a B-scan, which has to be further processed inorder to extract the needed information about the inspectedscene. In this framework, inversescattering-based approachesare gaining an ever-increasing interest, thanks to their capabilities of directly providing images of the physical and dielectricproperties of the investigated areas. In this paper, some advances in the development of such inversion techniques in theGPR field are revised and discussed.